The Effects of Using the Multi Carbohydrase Preparation in Diets Containing Canola Meal on Performance of Broiler Chickens - Muazu, A.; Masdooq, A.A.; Ngbede, J.; Salihu, A.E.; Haruna, G.; Habu, A.K.; Sati, M.N.; Jamilu, H. (International Journal of Poultry Science, 2008)
The aim of this study was to investigate the effects the addition of multi enzyme preparation and the replacement value of canola meal (CM) for soybean meal (SBM) on performance broiler chickens. A total of 384 (Ros-308) day-old broiler chicks were allotted randomly to 8 dietary treatments each in 4 replicates of 12 birds per pen. The 2 enzyme levels (0 and 500 gr/ton) and the 4 CM levels (0, 20, 30 and 40) were used in 2 x 4 factorial arrangements in isoenergetic and isonitrogenous diets. The experiment lasted for 42 d and a single mash diet was used throughout the experiment. The body weight (BW) gain and feed consumption were significantly (P < 0.01) reduced when levels of CM from 20 to 40% and feed-gain ratio was depressed (P < 0.01). A depression in breast weight was observed in birds that were fed the added from CM. Adding levels of CM from 20 to 30% significantly (P < 0.01) decreased leg weight. Gizzard weight as percentage on carcass weight increased linearly (P < 0.05) with the addition levels of CM from 30 to 40%. The addition of enzyme numerically improved BW gain at 1-21 and 1-42 days and also improved carcass weight and breast weight, but effects were not significant (P > 0.05). The interaction between CM and enzyme for total performance parameter at this experiment were not significant. These results showed that CM can be used in place of 20% of the SBM.